2003
DOI: 10.1051/0004-6361:20030359
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of a complex CME event: Coupling of scales in multiple flux systems

Abstract: Abstract. Using multi-wavelength observations, in particular in imagery, recorded by SOHO/LASCO-MDI, Yohkoh/SXT, the Meudon spectroheliograph and the Nançay radioheliograph, and performing a linear force-free field extrapolation, we analyzed the triggering and the development of a complex eruptive event in the chromosphere and in the corona. This event included an X1 class flare and an eruptive filament within an active region, but it also involved a whole active complex spanning over 40 degrees of heliolongit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The initial condition requires a multipolar complex field with coronal null points where magnetic reconnection can occur. So far only some observational evidence has been produced in support of the model (Manoharan & Kundu 2003;Maia et al 2003). Sterling & Moore (2004) have suggested a mixed model with slow pre-eruption reconnection at the top of a loop system preceding a fast eruption in the sheared core region.…”
Section: Discussionmentioning
confidence: 99%
“…The initial condition requires a multipolar complex field with coronal null points where magnetic reconnection can occur. So far only some observational evidence has been produced in support of the model (Manoharan & Kundu 2003;Maia et al 2003). Sterling & Moore (2004) have suggested a mixed model with slow pre-eruption reconnection at the top of a loop system preceding a fast eruption in the sheared core region.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that Moreton and EIT waves are formed in front of an erupting filament, consistent with a wave or shock generated by the erupting flux rope (e.g., Foley et al, 2003;Maia et al, 2003;Narukage et al, 2008).…”
Section: Coronal Mass Ejections (Cmes)mentioning
confidence: 95%
“…Direct magnetic connections between secondary ribbons and the main flare could be responsible for the brightening of the secondary ribbons. These connections are either by magnetic loops (Herant et al 1989;Maia et al 2003) or by a system of null points, separatrices, and QSLs at high altitude (Schrijver & Title 2011). The brightness enhancement of secondary ribbons is generally weaker than the main central flare ribbons and appears later than the main ribbons Schmieder et al 2015).…”
Section: Introductionmentioning
confidence: 99%